Ownership influence and CSR disclosure in China - Hu, Yuan Yuan; Zhu, Yanhui; Tucker, Jon; Hu, Yuxiao (Accounting research journal, 2018)
Purpose This paper aims to examine the relationship between ownership type and the likelihood of publication of a corporate social responsibility (CSR) report. Design/methodology/approach Drawing on stakeholder salience theory, the probit model is used for a sample of 1,839 Chinese listed firms to study how different types of owners influence firm CSR engagement. Findings The analysis reveals that the Chinese stock exchanges exert a positive influence on the likelihood of a firm producing a CSR report, an effect which is more significant in state-owned enterprises (SOEs). Foreign investors lead to a greater likelihood of publication of a CSR report, though this effect is weaker in SOEs. In contrast, the holdings of state and domestic institutional investors are broadly neutral. Practical implications The study helps corporate managers to recognise how particular types of shareholders will value their efforts regarding CSR activities and disclosure and also assists policymakers in improving the level of CSR disclosure through the development of new policy. Social implications Apposite CSR disclosure enhances trust and facilitates the shared values on which to build a more cohesive society. Originality/value The novelty of this study is that it addresses the effect of institutional investors on Chinese firm CSR engagement and thus provides an important insight for firms, investors and other stakeholders into the interplay of portfolio investment and CSR.